2001
DOI: 10.1002/etc.5620201131
|View full text |Cite
|
Sign up to set email alerts
|

Testing of metal bioaccumulation models with measured body burdens in mice

Abstract: Estimates of chemical accumulation in prey organisms can contribute considerable uncertainty to predictive ecological risk assessments. Comparing body burdens calculated in food web models with measured tissue concentrations provides essential information about the expected accuracy of risk indices. Estimates of arsenic, cadmium, copper, lead, and nickel body burdens in house mice (Mus musculus) inhabiting a seasonal wetland were generated with two small mammal bioaccumulation models. Published soil-to-small m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Soil-dwelling organisms inhabiting these areas are known to accumulate metals [1,2], and dietary transfer to predators such as shrews and moles has been observed [3,4]. Bioaccumulation studies have demonstrated that metal accumulation in small mammals can vary between the extremes of bioreduction and biomagnification [3][4][5][6][7][8][9], which complicates interpretation of field data and environmental risk assessment of metals.…”
Section: Introductionmentioning
confidence: 99%
“…Soil-dwelling organisms inhabiting these areas are known to accumulate metals [1,2], and dietary transfer to predators such as shrews and moles has been observed [3,4]. Bioaccumulation studies have demonstrated that metal accumulation in small mammals can vary between the extremes of bioreduction and biomagnification [3][4][5][6][7][8][9], which complicates interpretation of field data and environmental risk assessment of metals.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review located several studies reporting mercury concentrations in liver (Clark et al, 1992;Fortin et al, 2001;Lord et al, 2002;Porcella et al, 2004). Several other metal concentration studies also reported values for the liver (Neithammer et al, 1985;Hegstrom and West, 1989;Ma et al, 1991;Pascoe et al, 1994a;Laurinolli and Bendell-Young, 1996;Peles and Barrett, 1997;Nyangababo, 2001;Torres and Johnson, 2001b;Smith et al, 2002). Desert mammals have developed adaptations for survival in the desert, responding to extreme high and low temperatures, rapid evaporative water loss, and scarcity of water (Al-kahtani et al, 2004).…”
Section: Introductionmentioning
confidence: 99%